2022
DOI: 10.1098/rspb.2022.0696
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mean body size in an expanding population of a threatened species

Abstract: With some taxa, a reduction in the mean size of individuals may reflect over-harvesting and/or trophy hunting. However, we show that in sea turtles, a reduction in the mean size of breeding individuals may be part of the good news story of an expanding population. We describe a 70-fold increase in annual nest numbers on the island of Sal (Cape Verde, North Atlantic) between 2008 and 2020 (from 506 to 35 507 nests), making this now one of the largest loggerhead ( Caretta caretta ) nestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(64 reference statements)
2
13
0
Order By: Relevance
“…There was a clear decline in the mean size of nesting turtles at Aldabra from 1996 to 2016 that co-occurred with an increase in nesting numbers (Pritchard et al 2022), as has been reported in some other populations around the world, for example green turtles at Ascension Island (Weber et al 2014) and loggerhead turtles, Caretta caretta, in South Africa and the Cape Verde islands, respectively (Le Gouvello et al 2020;Hays et al 2022). At Ascension Island where overall nesting activity and numbers of egg clutches laid annually had increased by almost sixfold since 1977, the mean annual CCL of green turtle nesters declined from about 116 cm in 1970 to about 112 cm in 2010, i.e.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…There was a clear decline in the mean size of nesting turtles at Aldabra from 1996 to 2016 that co-occurred with an increase in nesting numbers (Pritchard et al 2022), as has been reported in some other populations around the world, for example green turtles at Ascension Island (Weber et al 2014) and loggerhead turtles, Caretta caretta, in South Africa and the Cape Verde islands, respectively (Le Gouvello et al 2020;Hays et al 2022). At Ascension Island where overall nesting activity and numbers of egg clutches laid annually had increased by almost sixfold since 1977, the mean annual CCL of green turtle nesters declined from about 116 cm in 1970 to about 112 cm in 2010, i.e.…”
Section: Discussionsupporting
confidence: 57%
“…a decrease of about 1 cm per decade (Weber et al 2014), compared to the decline in size of about 0.6 cm per decade that we recorded on Aldabra, where nesting activity has increased by more than threefold between 1980 and 2016 (Pritchard et al 2022). Mean size of nesters may be influenced by an increase in the number of first-time nesters (neophytes or recruits) that are presumably smaller than established nesters (remigrants) (Hays et al 2022). Likewise, in Hawaii (USA), Piacenza et al (2016) found evidence of directional changes in size over time, suggesting shifts in age structure that could be due to recruitment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The population’s growth depends on the recruitment of neophytes. In expanding populations, the proportion of neophytes is expected to increase over time [ 41 ] and this is often the case unless, for some unpredicted event (e.g., years with extreme temperatures, drought, and heavy rainfall affecting the incubation environment), the stock expected to recruit is completely or partially lost. It is assumed that the size of the females in a recovering population will be smaller than when populations were stable and had a balanced structure of all its components.…”
Section: Discussionmentioning
confidence: 99%